Hydrophone VSP imaging in the Agnew - Wiluna Belt, Western Australia - Greenwood, Andrew; Dupuis, Christian; Hashemi, Anousha; Urosevic, Milovan (CSIRO Publishing, 2010)
A Vertical Seismic Profiling (VSP) experiment using a 24 channel hydrophone array was conducted concurrently with a short 2D seismic section in the Agnew-Wiluna greenstone belt. The primary aim of this experiment was to test the applicability of borehole reflection seismology in a complex hard rock (HR) environment. The Agnew – Wiluna VSP field experiments produced high quality signal to noise ratio images. Through the use of Kirchhoff migration high angle structures were mapped with detail around the borehole for both near and far offset shots. Apparent dips in the surface seismic and in particular zero-offset VSP are in agreement with each other and appear to perfectly match foliation alignments observed in numerous core samples. Faults crossing the sections were better identified in the walk-away VSP experiment. These results show great promise for developing a cost effective high resolution seismic imaging technique at the localised mining scale.